Charting New Horizons in Teacher Education: How Practicum Students Empower and Support In-Service Teachers - Masoume Ahmadi; Nasser Sabourianzadeh; Mobina Nazari (Journal of Modern Research in English Language Studies)
Reciprocal learning, nurtured within a community of practice, is a cornerstone of teacher professional development. Despite extensive research on mentor-led support for student teacher (ST) professional development, the reciprocal potential of STs to transform and shape mentor teachers’ (MTs) practices remains largely unexplored. This study offers a comprehensive analysis of the distinct perspectives of practicum students (PSs) concerning their ability to empower and support in-service teachers, exploring the impact of STs on the professional development of their MTs. A maximum variation sampling technique was employed to recruit 57 Iranian STs from diverse majors at Farhangian University. All participants had completed a minimum of 10 weeks of supervised teaching practice sessions at schools. In-depth, focus-group interviews were conducted to collect data, and thematic analysis was adopted to analyze the data using NVivo software version 10. The results demonstrated how the STs, armed with new insights and pedagogical expertise, were invaluable collaborators in accelerating the professional development of their MTs. This collaboration was particularly evident in essential teaching competencies, such as communication, planning and organization, assessment, classroom management, and specialized knowledge and skills in the subject matter and technology. The findings reinforce the effectiveness of practicum placements in developing higherquality, in-service teacher-training programs. Policymakers and authorities are encouraged to consider these findings to improve the impact of STs in practicum courses, thereby promoting the overall quality of teacher education and teaching practices.